(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Palengke De Gulong is a proposed mobile market business offering wet and dry market goods. The main office of the company will be in Ninong Pedro St. BF Homes Phase III Deparo North Caloocan, City. The researchers randomly selected 100 respondents. The survey was conducted at BF Homes Phase III Deparo, Caloocan City. Part of the questionnaire asks for the profile but name are optional to protect the anonymity of the respondents. There are 10 questions utilized in the survey questionnaire using multiple choices, dichotomous, and scaling type of questions. These questions are structured to gather respondents’ preference on product price and promotional activities of the business. The result of the survey shows that the respondents’ product ranking for meat are in this order: fish, meat, vegetables, condiments and fruits. Most of the respondents preferred galunggong with 39% followed by tilapia with 35%. Most of the respondents agreed to buy market goods during Saturday with 43% while 21% preferred Sunday. Seventy-six percent of the respondents are interested to avail goods in a mobile wet and dry market. Weekly expense for market goods is 900pesos and above for 56% of respondents. Frequency of buying market goods are once a week with 46% and 44% for twice a week. Forty-six percent agreed that they are willing to pay cash on delivery while 63% are interested to avail pre-ordered products for celebrations and holiday seasons. Freebies preferred by the respondents are umbrella with 43% and ecobag with 23%. The researchers came up with a feasible business named, Palengke De Gulong. Marketing and promotional activities involves distribution of flyers, offering membership cards and freebies such as umbrella, mug, tumbler, eco bag and fan. This business aims to promote healthy lifestyle by making it convenient for consumers to buy market goods for preparation of their home cooked meals.